William T. Vollmann: The Art of Fiction CLXIII. - Bell, Madison Smartt (Paris Review)
Presents an interview with author William T. Vollmann. Rate of production; Work habits; Problems with carpal tunnel syndrome; Work as a computer programmer; Interest on Afghanistan; Influence of other writers.